Penyisipan Gambar Pada File Video Menerapkan Metode Two Sided Side Match - Ledi Firman Zendrato (TIN: Terapan Informatika Nusantara, 2022)
When entering a message into the message container it often leaks the message. Like the insertion of images in video files, there are often leaks of inserted image messages caused by irresponsible parties or intentionally leaking the messages contained. As a result, the message to be sent will change or the message to be sent cannot be sent because these people deliberately leaked the contents of the message sent. Insertion using the Two Sided Side Match method allows the secret message to be sent to be more secure, because this method uses two neighboring pixel values ​​to be able to predict how many messages will be inserted in a pixel. So that the insertion can be done in such a way and the image files that are inserted in the video cannot be hacked by irresponsible people. This research can produce security applications and image insertion data can be secured without containing suspicion so that data leaks do not occur